Privação de testosterona promove queda de contratilidade em músculos papilares isolados de ratos espontaneamente hipertensos (SHR): Papel do sistema renina angiotensina - Silva, Marito Afonso Sousa Costa (2019)
Testosterone plays an important role in cardiac function and in the functioning of the cardiovascular system. This function can be performed directly, with direct action on the cardiomyocyte and blood vessels, or also, via activation of the RAAS. Therefore, the compromise in its production, a common scenario in middle-aged men, is characterized as a risk factor for cardiovascular disease, such as the reduction of myocardial contractility. Considering the important relation testosterone deficiency and alteration of the activity of the RAAS, the objective was to investigate the effects of the treatment with telmisartan for 8 weeks on the contractility of papillary muscles of SHR OQT rats, evidenced the role of this drug in the kinetics of calcium. For this, SHR animals were divided into 5 groups: control group (Sham), orchiectomized (OQT) treated with vehicle, treated with telmisartan (OQT + Tel), orchiectomy treated with telmisartan plus PPAR-γ antagonist (OQT + Tel + BADGE) and orchiectomized rats treated with hydralazine (OQT + Hydra). OQT group showed a reduction in the contraction force of the papillary muscles that was prevented by the treatment with telmisartan and telmisartan + BADGE, similarly. Calcium inotropic response, as well as beta-adrenergic activation, were also reduced in the OQT group and prevented by treatment with telmisartan. It important to be noted that the treatment with telmisartan + BAGDE showed increased in the calcium inotropic response as well as in the beta adrenergic activation when compared to telmisartan treated OQT group. The contractions obtained after a 10-minute pause of electrical stimulation (PRC), which indirectly evaluates transarcolemal calcium inflow, were similar in papillary of OQT and SHAM rats. However, this response increased in the telmisartan treated OQT group and in the OQT group treated with telmisartan and BADGE, and was even higher in the latter group, suggesting that telmisartan treatment was able to increase trans-sarcolemmal calcium influx, regardless of the presence of telmisartan. orchiectomy. In addition, these results suggest that when the effect of telmisartan is only occur in AT 1 receptor blockade the strength improvement is even greater. An increase in the expression of SERCA2a and NCX was observed in the OQT group when compared to SHAM, which was prevented by treatment with telmisartan. In addition, treatment with telmisartan + BADGE prevented the increase of SERCA2a expression observed in the OQT group, without altering the increase of NCX expression evidenced in the OQT group. Protein expression of PLB was not altered in the OQT group, but treatment with telmisartan reduced the expression of this protein and the association of telmisartan + BADGE produced an even greater reduction compared to the other groups. However, the expression of the phosphorylated PLB was similar in all groups studied. The AT1 receptor protein expression was not altered by OQT but reduced after telmisartan treatment. Together, our results demonstrate that orchiectomy in hypertensive animals reduces contractility of papillary muscles, and the treatment with an SRAA receptor antagonist and PPARγ partial agonist (telmisartan) prevents the impairment of calcium response and beta adrenergic response observed in OQT rats, preventing the reduced of contraction force. In addition, it is suggested that the activation of PPAR-γ by telmisartan attenuates the transarcolemal calcium influx preventing a possible calcium overload due to an exclusive effect of telmisartan on AT1 receptor antagonism.